#TITLE_ALTERNATIVE# - IWAN GINTING (NIM : 10104095); Pembimbing : Dr. Janson Naiborhu
Stability of a system plays an extremely important part, so it has to be investigated carefully. However, determining stability of a system is not an easy task to do, especially when the system is nonlinear. Lyapunov’s method is an effective approach in doing it. This method is adapted from energy concepts. Lyapunov’s method can also be used to determine a region of attraction in which the system is stable, or in particular, asymptotically stable. Despite being an effective, this method still comes up short, especially in finding such a Lyapunov function that satisfies conditions to determine stability of a system. In this final project, some methods to construct Lyapunov function will be studied. Those methods are first integral, Krasovskii, variable gradient, and Zubov’s method.